The effect of photobiomodulation on the brain during wakefulness and sleep - Moro, Cecile; Valverde, Audrey; Dole, Marjorie; Hoh Kam, Jaimie; Hamilton, Catherine; Liebert, Ann; Bicknell, Brian; Benabid, Alim-Louis; Magistretti, Pierre; Mitrofanis, John (Frontiers in Neuroscience, 2022)
Over the last seventy years or so, many previous studies have shown that photobiomodulation, the use of red to near infrared light on body tissues, can improve central and peripheral neuronal function and survival in both health and in disease. These improvements are thought to arise principally from an impact of photobiomodulation on mitochondrial and non-mitochondrial mechanisms in a range of different cell types, including neurones. This impact has downstream effects on many stimulatory and protective genes. An often-neglected feature of nearly all of these improvements is that they have been induced during the state of wakefulness. Recent studies have shown that when applied during the state of sleep, photobiomodulation can also be of benefit, but in a different way, by improving the flow of cerebrospinal fluid and the clearance of toxic waste-products from the brain. In this review, we consider the potential differential effects of photobiomodulation dependent on the state of arousal. We speculate that the effects of photobiomodulation is on different cells and systems depending on whether it is applied during wakefulness or sleep, that it may follow a circadian rhythm. We speculate further that the arousal-dependent photobiomodulation effects are mediated principally through a biophoton - ultra-weak light emission - network of communication and repair across the brain.